Stress and Work Engagement: A Conceptual Study on Academics in Malaysian Private Universities - Latif, Ummi Khaira; Kusumasari, Tien Fabrianti; Sheikh Khairuddin, Sheikh Muhamad Hizam; Nadzri, Firdaus Hilmi (International Journal of Innovation in Enterprise System, 2017)
There is an abundance of studies on work engagement found in the literature. However, there is a lack of grounded research framework to be based on relating stress to work engagement of Malaysian private academics. Therefore, this study is aimed at 1). reviewing the literature on stress and work engagement; 2). applying the ASSET model of stress to work engagement; 3). hypothesizing the relationships among these variables, and 4). deriving a conceptual framework. Based on the literature review on psychological literature and the application of the ASSET model of stress, the paper proposes a model of the relationship between stress and work engagement through commitment and health. Suggestions for practice and future research are also presented. Keywords— ASSET, Malaysian private academics, stress, work engagement.